Upaya Mewujudkan Sekolah Bebas Bullying Dengan Sosialisasi Dan Pendampingan Penyelesaian Bullying Di MI Darussalam - Pristiwiyanto, Pristiwiyanto; Hidayah, Julistian Nurul; Mukminah, Sevira Silakhul; Anggraeni, Novika Mita; Fadil, Nur (LPPM, STAI Al-Azhar Menganti, 2023)
This research aims to determine the impact of bullying, the factors that cause bullying, and the Al Azhar Institute's assistance efforts in dealing with bullying among students. The method used is qualitative, namely observation and lecture methods. The results of the research showed that the form of bullying that occurred was physical bullying in the form of punches, teasing between friends, apart from that, verbal bullying in the form of cheering and calling other students special names. The causal factors are family factors, peers and the social environment. And the efforts of the assistance of the Al Azhar Institute and MI Darussalam in dealing with bullying among students is to implement social control in the form of prevention, by holding student self-development activities, socializing bullying and discipline.